Characteristics of Mocaf (Modified Cassava Flour) From Cassava (Manihot utilissima): Study of Tape Yeast Concentration and Fermentation Time: Karakteristik Tepung Mocaf (Modified cassava flour) dari Singkong (Manihot Utilissisma): Kajian Konsentrasi Ragi Tape dan Lama Fermentasi - Ningrum, Wiwin Ekawati; Saidi, Ida Agustini (Procedia of Engineering and Life Science, 2023)
Cassava is a local food that has low shelf life. Mocaf flour is processed cassava which is modified by fermentation. This study used a randomized block design (RBD) method with 3 repetitions. With the treatment of tape yeast concentration which consists of 3 levels, namely 1%, 1.5% and 2% and the treatment of fermentation time with 3 levels, namely 24 hours, 48 hours, and 72 hours. Data were analyzed using ANOVA then continued with the BNJ test with a level of 5%. As well as the hedonic scale scoring organoleptic test. The results showed that the highest value for the color parameter L was 296.66, color a was 5.17, color b was 34.21, organoleptic aroma was 188, organoleptic color was 167.5.